Fluorescence decay analysis using expotential compensation deconvolution - Salami, Momoh Jimoh Eyiomika; Khalifa, Othman Omran; Jibia, Abdussamad Umar (2010)
Fluorescence decay experiments is one of the major sources of transient multiexponential signals. A new method for the analysis of fluorescence decay experimental data is proposed. The method relies on the classical Gardner transform to convert the data signal into a convolution model which is deconvolved using exponential compensation deconvolution technique. Eigenvector algorithms are then used to further model the resulting complex exponentials to obtain better estimates of decay rates and number of components. Simulation and experimental results show that this method outperforms previous approaches if the truncation point of the deconvolved data is correctly selected.